Gender Problems in Indonesia: The phenomenon of gamophobia in a permissive society - Khamdan Safiudin; Rasheedat Modupe Oladimeji (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2024)
The global discourse on sexual recession has intensified alongside the increasing trend of singlehood. The decline in the global population reflects this transformation, while a significant proportion of millennials tend to avoid marriage and long-term commitment. This study aims to analyze gamophobia as a multidimensional phenomenon reflecting permissivism, psychosocial threats, and patriarchal gender constructions. The study employed a literature review approach with critical analysis of academic sources related to gamophobia, gender, and permissivism. Data were analyzed thematically through source triangulation to generate valid findings regarding social, psychological, and gender dynamics in modern society. The findings reveal three major issues: (1) Gamophobia among millennials reflects permissivism, in which personal freedom, career orientation, and self-development are prioritized over marriage and family resilience; (2) Gamophobia triggers isolation, depression, declining birth rates, weakened family resilience, and demographic instability as consequences of shifting modern social values; and (3) Gamophobia is shaped by patriarchal constructions and relational inequality, thus requiring pre-family resilience through emotional readiness and premarital commitment. This study concludes that gamophobia represents a multidimensional social crisis driven by permissivism, gender inequality, and changing modern values, resulting in declining marriage rates, psychosocial vulnerability, and weakened family and demographic resilience. The study contributes by integrating permissivism and gender perspectives into gamophobia studies while proposing pre-family resilience as a preventive strategy through emotional readiness, self-efficacy, premarital education, and the reinforcement of moral values to foster more stable family relationships.